PENGGUNAAN CAMPUR KODE OLEH KELUARGA DARI PERKAWINAN ANTARBANGSA DI DAERAH PARIWISATA LOVINA - Ni Luh Putu Sri Adnyani (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2010)
The present study aims at finding out 1) words from other languages especially Englishwhich occur in Indonesian discourse and 2) Indonesian words which occur in Englishdiscourse used by mixed marriages family in the tourism area of Lovina. To reach theabove purposes, the data was collected through partisipant observation and analyseddescriptively. The result of the study shows that both Indonesian-English and English-Indonesian code mixing used by the family related to activities done by them such ashaving meal, doing out door activities, and school related topics. The English wordswere used in Indonesian discourse because it was almost imposible or far too complicatedto describe the mention things in Indonesian such as things related to food. Thiswas also the case found when Indonesian words were used in English discourse. Both English and Indonesian words consist of noun, verb, and adjectives.